Preservation of neuronal function as measured by clinical and MRI endpoints in relapsing-remitting multiple sclerosis: how effective are current treatment strategies?. (4th March 2018) - Graetz, Christiane; Groppa, Sergiu; Zipp, Frauke; Siller, Nelly
ABSTRACT: Introduction : Approved medications for relapsing-remitting multiple sclerosis have shown to be effective in terms of their anti-inflammatory potential. However, it is also crucial to evaluate what long-term effects a patient can expect from current MS drugs in terms of preventing neurodegeneration. Here we aim to provide an overview of the current treatment strategies in MS with a specific focus on potential neuroprotective effects. Areas covered : Randomized, double-blind and placebo or referral-drug controlled phase 2a/b and phase 3 trials were examined; non-blinded phase 4 studies (extension studies) were included to provide long-term data, if not otherwise available. Endpoints considered were expanded disability status scale, various neuropsychological tests, percent brain volume change and T1-hypointense lesions as well as multiple sclerosis functional composite, confirmed disease progression, and no evidence of disease activity. Expert commentary : Overall, neuroprotective functions of classical MS therapeutics are not sufficiently investigated, but available data show limited effects. Thus, further research and development in neuroprotection are warranted. When counselling patients, potential long-term beneficial effects should be presented more conservatively.